2022
DOI: 10.1080/16549716.2022.2101731
|View full text |Cite
|
Sign up to set email alerts
|

Survival patterns of neonates born to adolescent mothers and the effect of pregnancy intentions and marital status on newborn survival in Kenya, Uganda, and Tanzania, 2014–2016

Abstract: Background Adolescent pregnancy and associated neonatal mortality are major global health challenges. In low-income settings where 90% of the 21 million global adolescent pregnancies occur, half are unintended and a fifth experience unsafe abortion. In Kenya, Uganda, and Tanzania, the survival patterns of neonates born to adolescents are unclear. Objectives To assess survival patterns among neonates born to adolescents and the effect of pregnancy intentions and marital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…In urban areas, there were higher likelihoods of neonatal mortality among mothers aged less than 20 years with reference to mothers aged 20 to 34 years. The findings in urban areas relate to findings of other studies (Akinyemi et al, 2015;Woodall & Driscoll, 2020;Arunda et al, 2022;Wardani et al, 2022). A nationwide study conducted in Nigeria by Akinyemi et al (2015) found hazard ratios of 1.75 and 1.50 comparing neonatal deaths among adolescent mothers to mothers aged 20 to 35 years.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In urban areas, there were higher likelihoods of neonatal mortality among mothers aged less than 20 years with reference to mothers aged 20 to 34 years. The findings in urban areas relate to findings of other studies (Akinyemi et al, 2015;Woodall & Driscoll, 2020;Arunda et al, 2022;Wardani et al, 2022). A nationwide study conducted in Nigeria by Akinyemi et al (2015) found hazard ratios of 1.75 and 1.50 comparing neonatal deaths among adolescent mothers to mothers aged 20 to 35 years.…”
Section: Discussionsupporting
confidence: 83%
“…The USA national report indicated that neonatal mortality rate was 121.67 percent higher among teenage mothers compared to mothers aged 20 to 29 years (26.6 versus 12.0 deaths per 1,000 live births) (Woodall & Driscoll, 2020). A study done in Kenya, Uganda and Tanzania by Arunda et al (2022) found the adjusted hazards ratio of death among neonates born to mothers aged less than 20 years to be 0.86 times higher compared to those born to mothers aged 20 to 29 years (aHR = 1.86; 95% CI = 1.06 -3.29). In support of these findings, a key informant said: "The younger mothers may not be well experienced: it could be a case of unintended pregnancy or a case of sexual violence.…”
Section: Discussionmentioning
confidence: 99%
“…Desire for pregnancy. Of the eight studies [25,27,42,51,63,67,68,81] that examined desire for pregnancy for pregnancy and risk of mortality, only one [81] found an association. Arunda et al found that there was the highest risk in neonatal mortality among adolescent mothers who had unintended pregnancies in marital union [81].…”
Section: Proximate Factorsmentioning
confidence: 99%
“…Second, we did not include incremental risks of neonatal mortality or child morbidity for children born as a result of unintended pregnancy. In our literature search, we found mixed results on the impact of unintended pregnancies on health outcomes of the child ( 55 57 ). In some cases, women were less likely to indicate a pregnancy was unwanted if it ended in neonatal death ( 57 ).…”
Section: Discussionmentioning
confidence: 97%